Pelatihan Pembuatan Konten Media Sosial Menggunakan Teknologi Ai Untuk Mendapatkan Passive Income Bagi Siswa Smk di Cikarang - Sanjaya, Memet (Program Studi Bisnis Digital - Fakultas Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the improvement of digital literacy and AI-based content production skills among vocational high school (SMK) students through structured training. The research employed a quantitative approach using a one-group pretest–posttest design. A total of 33 students participated in the training, while 22 paired responses met the criteria for statistical analysis. The research instrument consisted of Likert-scale questionnaires and open-ended questions measuring content creation skills, AI knowledge, perceptions of the economic potential of digital content, and experience using AI tools. Data were analyzed using the Wilcoxon Signed Rank Test due to non-normal data distribution. The results indicate a statistically significant improvement across all measured indicators, with p-values < 0.001. These findings demonstrate that structured AI-based training is effective in enhancing digital literacy and preparing vocational students to produce economically valuable digital content. This study contributes empirical evidence to the development of AI-based digital literacy learning models in vocational education.